Sensory Analysis and Food Safety, Role in The Marketing of Innovative Foods – Cheeses Fortified with Algae - Mirela Gianina CALU; Violeta GAGU (LEOCĂ); Gheorghe Adrian ZUGRAVU; Silviu Cristian SIMIONESCU (Communications of International Proceedings, 2023)
A continuous challenge in recent years has been the study of algae - plant organisms with nutritional value and extremely valuable chemical content. This paper seeks to highlight the contribution   of   sensory  analysis   combined   with   food  safety  in  the   consumption   of   cheesefortified with algae. Quality is a dynamic concept, due to the demands of consumers in relationto the development of areas of activity and technical-scientific progress. Quality, the nodal center of food product analysis, represents a set of attributes and characteristics  of a product that determine  its  acceptance  or  refusal  to  be  used  in  meeting   requirements  imposed   from  the research  and design phase. For cheese, the components  of  quality are: nutritional,  sensory, hygienic, and aesthetic value. All five senses - visual, tactile, auditory, gustatory, and olfactory -are involved in the sensory analysis of cheeses. The first three provide responses regarding appearance, consistency, and partially, texture, while the last two are essential in identifying andaccepting cheeses.
Keywords: food safety; sensory analysis; multisensor analysis